Proline-catalyzed asymmetric synthesis of syn- and anti-1,3-diamines - Kumar, Pradeep; Jha, Vishwajeet; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2013)
A general organocatalytic strategy for asymmetric synthesis of both syn/anti-1,3-diamines has been developed. The strategy employs proline-catalyzed sequential alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step where syn-1,3-diamine was obtained as the most favorable product.